2021
DOI: 10.21776/ub.jppbr.2021.002.02.5
|View full text |Cite
|
Sign up to set email alerts
|

Borderline Personality Disorder During Covid-19 Pandemic

Abstract: The COVID-19 pandemic has had a significant impact on patients diagnosed with Borderline Personality Disorder (BPD). BPD patients who are unable to see a therapist due to limitations during the pandemic may experience feelings of uncertainty, misperceptions, misunderstandings, and even paranoid ideas that are usually associated with stress. In patients who have previously undergone psychotherapy, there may be negative effects during this pandemic. The majority of providers/therapists, on the other hand, stated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 20 publications
0
2
0
1
Order By: Relevance
“…Our study showed that three personality traits, dependent, antisocial, and borderline, were more prevalent among intensive care professionals who were COVID-19 positive. In this respect, Yudhantara et al's [29] results were similar to ours. Starcevic et al [30] suggest that high levels of neuroticism constitute a risk for pandemic-induced distress and poor overall coping.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Our study showed that three personality traits, dependent, antisocial, and borderline, were more prevalent among intensive care professionals who were COVID-19 positive. In this respect, Yudhantara et al's [29] results were similar to ours. Starcevic et al [30] suggest that high levels of neuroticism constitute a risk for pandemic-induced distress and poor overall coping.…”
Section: Discussionsupporting
confidence: 88%
“…Pandemic conditions have prolonged social restrictions, severely impacting daily routines and leading to increased social isolation. These constraints on social interaction can contribute to emotional dysregulation and difficulties in interpreting the emotional cues of others, potentially resulting in borderline personality traits [29]. Our study showed that three personality traits, dependent, antisocial, and borderline, were more prevalent among intensive care professionals who were COVID-19 positive.…”
Section: Discussionmentioning
confidence: 66%
“…For example, Broadbear et al (2021) reported that most therapists found engaging with their patients difficult. Similarly, in their review, Yudhantara and Istiqomah (2021) suggested the possibility of worsening in BPD patients' well-being during the pandemic. Based on previous studies (e.g., Calati et al, 2019;Henry et al, 2021), the authors hypothesized that the experience of being isolated (due to the restrictions) might increase the risk of suicidal ideations and behaviors as well as self-harm.…”
Section: Discussionmentioning
confidence: 99%
“…1 Skizofrenia adalah gangguan pada otak dan pola pikir, skizofrenia mempunyai karateristik dengan gejala positif dan negatif. 2 Gejala positif antara lain (delusi, halusinasi, waham), disorganisasi pikiran dan gejala negatif seperti (sikap apatis, bicara jarang, afek tumpul, menarik diri dari masyarakat dan rasa tidak nyaman). Salah satu gejala skizofrenia adalah risiko perilaku kekerasan.…”
Section: Pendahuluanunclassified